(untitled) (LACCEI, 2024)
The costs for energy consumption in agro-industrial companies can be equivalent to more than 50% of production costs0 This is why the efficient use of electrical energy is important for the optimization of utilities. The objective of this work is to reduce energy costs, based on the ISO 50001 Standard, in refrigeration systems, in order to increase the profitability of the company. With a proactive diagnostic design, a survey was carried out on the head of operations and an evaluation of the electric motors of the refrigeration systems. It was found that the company did not have an energy management system and that the motors were of low efficiency with an efficiency between 0.6 and 0.8. Within the proposal, an energy management plan was developed0 and the acquisition of three premium efficiency motors with an efficiency of 0.95 was determined. Finally, with the implementation of the proposal, it is expected to reduce energy costs by 20.05% and increase profitability over sales by 6%. In the economic evaluation of the proposal, a VAN of 55,781.51, an IRR of 49% and a PRI of 2.97 years were determined.